The Dark Lord's daughter - Wrede, Patricia C., 1953- (Random House Children's Books, 2023)
"Kayla is just an ordinary girl . . . or so she thinks. When a day at the state fair is interrupted by the news that she's the daughter of a "Dark Lord," she and her family are quickly whisked to another world--one that's chock-full of magic but lacking in technology! As her family encounters fantastical creatures in place of their Earthly gadgets, Kayla must prepare for the unpreparable: meeting her father, the Dark Lord himself, for the very first time. All Kayla wants is to go home, but she must learn magic to do so. The catch? For the Dark Lord's daughter, the road to mastering magic is filled with evil traditions. As she ventures closer to her father, Kayla must decide whether to accept her birthright. Is she destined for darkness? Or can she become a new kind of Dark Lady?" --